Exploring English Language Teacher Identity Construction in Disadvantaged Chilean Schools through Textbook Usage - Victor Birkner (Colombian Applied Linguistics Journal)
Although the notion of English language teacher identity has drawn increasing interest in the literature, little is known about how teachers of English construct identities in disadvantaged settings. This study explored how three teachers of English in disadvantaged Chilean public schools construct identities and exercise agency while using prescribed textbooks. The investigation used a narrative inquiry methodology and was positioned within a sociocultural paradigm. Based on semi-structured online interviews, thematic narrative analysis was used to analyze the data collected. The findings suggest that teachers construct various identities as textbook users depending on their previous experience, level of professional development, and interactions with textbooks. According to the research, teachers exercise agency to construct new identities as textbook users by drawing on two temporal aspects that include prior experiences as English language learners and a mental image of the kind of teacher they want to become. Professional development and textbook interaction may also influence the construction of identities regarding textbook use. The article concludes with suggestions for language teachers and English language teacher education.